The Practice of Local Wisdom of Dayak People in Forest Conservation in South Kalimantan - Fahrianoor Fahrianoor; Tri Windari; Taharuddin Taharuddin; Ruslimar'i Ruslimar'i; Maryono Maryono (Center for Journal Management and Publication, 2013)
The research is conducted in the purpose of discovering the practice of local wisdom in Dayak people in their interaction with the forest. The research is also conducted using qualitative method, conceptual foundation focusing on local wisdom based in the community of Dayak Upau, Dayak Warukin and Dayak Loksado. The result shows that the practice of local wisdom in preserving the forest is by treating the nature in the way as treating the people themselves. The practice of local wisdom by the Dayaks is implemented in the forms of livelihood, social values, their knowledge and belief.